Urban Regeneration of Large Housing Estates in Europe: Hamburg and Niš Narratives. - (:unkn) unknown (My University, 2020)
As a response to rapid urbanization, the construction and expansion of Large Housing Estates (LHEs) have played a significant role in housing provision throughout Europe. These housing developments were constructed mostly at city outskirts and overtime have been concerned with social decline due to the concentration of lower-income, vulnerable and marginalized groups of people complemented with cuts in public expenditure and liberalization. As a result, LHEs face often-social problems and are viewed with skepticism and negativism. In contrast, in Central and Eastern Europe and particularly in former socialist countries, LHEs are still seen as a desirable housing environment until today. Nevertheless, there have been great concerns as well as the decline of LHEs in the post-socialist era. These concerns are focused on issues related to ownership and lack of maintenance, as a result of the political, economic and social transition of post-socialist countries. On the micro-level of housing projects, residents and local actors have been interpreting marketization into their daily practices and decisions, which shaped different LHEs transformation types. In post-socialist Serbia, as in other transition countries, the city of Niš has experienced the same urban regeneration challenge of LHE. The former state-owned property was privatized to the sitting tenants in a low price form. The rapid withdrawal of the state from housing sector in the early phase of transition raised a set of issues, and led to different transformation types, such us, new infill housing and commercial development, expansion of multi-storey extensions, transformation and adaptation of garages and increase in commercial functions ''garage capitalism'', the quantitative and qualitative decrease of public open spaces, as well as a wide range of individual, building-based transformation. Difficulties to afford flats maintenance and renovation, as well as to refurbish entire blocks, are also present. The participation of society is necessary for the successful implementation of integrated and sustainable development concepts. This document presents oral and visual narratives from Niš and Hamburg and reflects on both experiences in an effort to better understand the complexities of urban transformation in post-socialist cities, and to link them to the urban renewal processes of those similar in Western European cities.
Keywords: Großwohnsiedlung; Stadtrandsiedlung; Benachteiligter Stadtteil; Wohnsoziologie; Stadtsoziologie; Stadterneuerung; Bilddokumentation; Interview; Bewohner; Internationaler Vergleich; Studentenarbeit